2020
DOI: 10.3390/polym12091942
|View full text |Cite
|
Sign up to set email alerts
|

A Modified 3D-QSAR Model Based on Ideal Point Method and Its Application in the Molecular Modification of Plasticizers with Flame Retardancy and Eco-Friendliness

Abstract: The addition of plasticizers makes plastics flammable, and thus, poses a potential risk to the environment. In previous researches, plasticizers with flame retardancy had been synthesized, but their eco-friendliness had not been tested or described. Thus, in this paper, eco-friendliness plasticizers with flame retardancy were designed based on phthalic acid esters (PAEs), which are known as common plasticizers and major plastic additives. For a comprehensive analysis, such as flammability, biotoxicity, and enr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 45 publications
2
3
0
Order By: Relevance
“…In the CoMFA, CoMSIA1 and CoMSIA2 models evaluated in this study, the contribution rate of the S and the H accounted for 58.4%, 69.6%, and 71.6% (Table 2), respectively, suggesting that the non-specific reactions account for a larger proportion in the toxic effects of PAEs. The results of this study were consistent with other QSAR study on PAE biotoxicity and flammability which has shown that the hydrophobicity of molecules was an important parameter to characterize the toxicity of compounds [33]. This study also tried to apply the CoMSIA method to include the hydrogen bond donor and acceptor properties of the molecule.…”
Section: Ld 50 3d-qsarsupporting
confidence: 88%
See 1 more Smart Citation
“…In the CoMFA, CoMSIA1 and CoMSIA2 models evaluated in this study, the contribution rate of the S and the H accounted for 58.4%, 69.6%, and 71.6% (Table 2), respectively, suggesting that the non-specific reactions account for a larger proportion in the toxic effects of PAEs. The results of this study were consistent with other QSAR study on PAE biotoxicity and flammability which has shown that the hydrophobicity of molecules was an important parameter to characterize the toxicity of compounds [33]. This study also tried to apply the CoMSIA method to include the hydrogen bond donor and acceptor properties of the molecule.…”
Section: Ld 50 3d-qsarsupporting
confidence: 88%
“…Generally speaking, the hydrophobicity of a molecule was closely related to the stereo field. Our results found that the changes in LD 50 , IC 50 or Nrf2 were closely related to the hydrophobic field and the steric field, and the proportions were very large with the results like previous studies [33]. In fact, the hydrophobicity and volume of the groups had the most obvious effect on toxicity towards the HepG2 cells and Nrf2 expression.…”
Section: Nrf2 3d-qsarsupporting
confidence: 80%
“…CoMFA and CoMSIA models established using SYBYL-X2.0 software were used to analyze the differences of molecular fields around compounds. 21 Then, the effects of molecular active groups on biological activity were predicted by analyzing three-dimensional equipotential fields such as the electrostatic field, three-dimensional field, hydrophobic field, hydrogen bond donor field and hydrogen bond acceptor field, which provided the basis for designing new compounds. 19,22…”
Section: Molecular Optimization and Alignmentmentioning
confidence: 99%
“…The effects of solvation and derivatization on the UV absorption intensities were analyzed. Zhang et al [27] used the ideal point method, a flammability,…”
mentioning
confidence: 99%